Toxin–antitoxin operon kacAT of Klebsiella pneumoniae is regulated by conditional cooperativity via a W-shaped KacA–KacT complex. Issue 14 (1st July 2019) - Qian, Hongliang; Yu, Hao; Li, Peifei; Zhu, E; Yao, Qingqing; Tai, Cui; Deng, Zixin; Gerdes, Kenn; He, Xinyi; Gan, Jianhua; Ou, Hong-Yu
Abstract: Bacterial toxin–antitoxin pairs play important roles in bacterial multidrug tolerance. Gcn5-related N-acetyltransferase (GNAT) toxins inhibit translation by acetylation of aminoacyl-tRNAs and are counteracted by direct contacts with cognate ribbon–helix–helix (RHH) antitoxins. Our previous analysis showed that the GNAT toxin KacT and RHH antitoxin KacA of Klebsiella pneumoniae form a heterohexamer in solution and that the complex interacts with the cognate promoter DNA, resulting in negative autoregulation of kacAT transcription. Here, we present the crystal structure of DNA-bound KacAT complex at 2.2 Å resolution. The crystal structure revealed the formation of a unique heterohexamer, KacT–KacA2 –KacA2 –KacT. The direct interaction of KacA and KacT involves a unique W-shaped structure with the two KacT molecules at opposite ends. Inhibition of KacT is achieved by the binding of four KacA proteins that preclude the formation of an active KacT dimer. The kacAT operon is auto-regulated and we present an experimentally supported molecular model proposing that the KacT:KacA ratio controls kacAT transcription by conditional cooperativity. These results yield a profound understanding of how transcription GNAT–RHH pairs are regulated.